Pengaruh Overconfidence Bias dan Herding Bias terhadap Pengambilan Keputusan Gen Z di Kota Padang dalam Berinvestasi di Pasar Saham Indonesia - Muhammad Qodrie Andhika Saja; Eka Fauzihardani (Jurnal Eksplorasi Akuntansi, 2024)
This study seeks to investigate the impact of overconfidence and herding biases on the investment decision-making process among Generation Z individuals in Padang City. Conducted through survey research using a questionnaire to collect primary data, responses were gathered from 400 participants, including employees, students, and high school students aged 20-29 years. The statistical analysis employed for this research is multiple regression analysis. The findings reveal a significant positive correlation between overconfidence bias and the investment decision-making of Generation Z in Padang City. Additionally, herding bias also exhibits a notable positive influence on the decision-making of this demographic. The implications of this study aim to prompt readers, particularly Generation Z individuals considering investments in the Indonesian stock market, to approach decision-making with greater caution to minimize potential risks, especially for those new to investment endeavors.